Effect-based assessment of recipient waters impacted by on-site, small scale, and large scale waste water treatment facilities – combining passive sampling with in vitro bioassays and chemical analysis. Issue 1 (December 2018) - Rosenmai, Anna; Lundqvist, Johan; Gago-Ferrero, Pablo; Mandava, Geeta; Ahrens, Lutz; Wiberg, Karin; Oskarsson, Agneta
Abstract Waste water treatment facilities are a major sources of organic micropollutants (MPs) in surface water. In this study, surface water samples were collected from seven sites along a river system in Uppsala, Sweden, during four seasons and evaluated based on the occurrence of MPs in the samples and bioactivity usingin vitro bioassays. The sampling sites were differentially impacted by on-site sewage treatment facilities (OSSFs), small scale, and large scale waste water treatment plants (WWTPs). The bioassays used included activation of aryl hydrocarbon receptor (AhR), estrogen receptor (ER), nuclear factor kappa-light-chain-enhancer of activated B cells (NFkB), nuclear factor erythroid 2-related factor 2 (Nrf2), and androgen receptor (AR). Occurrence of 80 MPs, were analyzed using liquid chromatography coupled to tandem mass spectrometry. Most water samples induced AhR activity, and all sampling sites showed a similar profile regarding this activity. With the exception of one water sample, we did not detect any NFkB, Nrf2 or AR activity of the water samples. The exception was a sample impacted by OSSFs, which showed an activity in multiple bioassays, but the activity could not be explained by the occurrence of target MPs. The occurrence of MPs showed a spatial trend, with the highest number and amount of MPs detected in the samples collected downstream of the WWTPs, where up to 47 MPs were detected in one single sample. A seasonal variation was observed with highest levels of MPs and highest AhR activities in samples collected in June and September 2015. However, neither the seasonal activity nor the on-site activity could be explained by the measured MPs, suggesting unknown contributory agents in the water.